Penerapan Model Pembelajaran Problem Based Learning (PBL) Berbantuan Media Wordwall pada Materi Peluang untuk Meningkatkan Hasil Belajar Peserta Didik SMA Negeri 9 Surabaya - Nur Aini Ayu’ Fistanti; Anik Kirana; Fitria Indahwati (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
Learning outcomes are a series of skills, knowledge, attitudes and values ​​obtained by students in their thinking process during learning activities. This research aims to improve the learning outcomes of class X-4 students on opportunity material by applying the problem based learning model assisted by wordwall media. To see an increase in learning outcomes, classroom action research was carried out for two cycles using the method of observation and analysis of test results with research instruments in the form of pretest posttest questions in the 2023/2024 academic year. The subjects of this classroom action research were 34 students from class X-4 at SMA Negeri 9 Surabaya. The research results showed a consistent increase in learning outcomes over two cycles in the opportunity material. Before the action was taken there were 18 students who had not reached the KKM and only 16 students had completed it so the percentage of completion was 47.05% with an average learning outcome of 67.76. In the first cycle, the number of students who completed their learning outcomes reaching the KKM increased to 28 with a completion percentage of 82.35% and an average learning outcome of 78.23. In cycle II, the number of students whose learning outcomes achieved the KKM consistently increased so that there were 31 with a completion percentage of 91.17% and an average learning outcome of 89.54.